2024
DOI: 10.1371/journal.pone.0302720
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators of adherence to low-dose aspirin during pregnancy: A co-produced systematic review and COM-B framework synthesis of qualitative evidence

Raya Vinogradov,
Eleanor Holden,
Mehali Patel
et al.

Abstract: Introduction Women at increased risk of developing pre-eclampsia are advised to take a daily low-dose of aspirin from 12 weeks of pregnancy to reduce their risks. Despite the well-established prophylactic effect of aspirin, adherence to this therapy is low. This systematic review aimed to summarise evidence on the barriers and facilitators of adherence to low-dose aspirin to inform intervention development to support decision making and persistence with aspirin use for pre-eclampsia prevention. Materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…A survey about barriers and facilitators faced by midwives in the United Kingdom showed that conflicting views and deficits in resources hindered the implementation of aspirin 22 . A systematic review on counselling about aspirin revealed three categories predicting the success of implementation of aspirin: capability, motivation and opportunity 23 .…”
Section: Introductionmentioning
confidence: 99%
“…A survey about barriers and facilitators faced by midwives in the United Kingdom showed that conflicting views and deficits in resources hindered the implementation of aspirin 22 . A systematic review on counselling about aspirin revealed three categories predicting the success of implementation of aspirin: capability, motivation and opportunity 23 .…”
Section: Introductionmentioning
confidence: 99%